Pengaruh Layanan Konseling Kelompok pada Perilaku Korban Perundungan di SMK Negeri 1 Bogor - Ahiruddin Ahiruddin; Harun Rasyid; Ridwan Dwi Prasetyo (Journal on Education, 2023)
Bullying in school often occurs due to factors such as seniority, orientation period dynamics, and power dynamics. This will continue due to the lack of action taken to address the issue. The impact that bullying has on victims is significant and far-reaching. Adolescents who are victims of bullying are at a very high risk of experiencing physical and mental health problems. Victims of bullying are more likely to suffer from mental problems such as depression, anxiety, and fear, as well as physical issues such as headaches, indigestion, and muscle tension. This can lead to decreases in academic and non-academic achievements, as well as a loss of motivation and enthusiasm for learning. In extreme cases, victims of bullying may even commit suicide. The importance of having experts who can address bullying behavior is evident in the cases above. Guidance and counseling teachers are experts who can help to minimize or eliminate bullying behavior. This research was a quantitative survey conducted with 102 students of class XI at SMK Negeri 1 Bogor. The data was collected through a questionnaire and then analyzed using simple linear regression analysis. The results showed that information services had a significant effect on efforts to prevent bullying in students.